Interventional Oncology Approach to Hepatic Metastases - O'Leary, Cathal; Soulen, Michael C.; Shamimi-Noori, Susan (Seminars in Interventional Radiology, 2020)
Metastatic liver disease is one of the major causes of cancer-related morbidity and mortality. Locoregional therapies offered by interventional oncologists alleviate cancer-related morbidity and in some cases improve survival. Locoregional therapies are often palliative in nature but occasionally can be used with curative intent. This review will discuss important factors to consider prior to palliative and curative intent treatment of metastatic liver disease with locoregional therapy. These factors include those specific to the tumor, liver function, liver reserve, differences between treatment modalities, and patient-specific considerations.
Keywords: hepatic metastases; locoregional therapy; transarterial therapy; ablation; liver reserve